Uji Fitokimia dan Toksisitas Ekstrak Kloroform Kulit Batang Melochia umbellata (Houtt.) Stapf var. Visenia dengan Metode Bhrine Shrimp Lethality Test (BSLT) - Aeni HM, Nur; Soekamto, Nunuk H.; Firdaus, Firdaus (Indonesian Journal of Chemical Research, 2017)
Paliasa plants Melochia umbellata (Houtt.) Stapf var. Visenia is classified into species M.umbellata (Houtt.) Stapf which was potent to heal various of illness. The aim of this research to know secondary metabolites and its toxicity from extract chloroform stem bark of M. umbellata (Houtt.) Stapf var. Visenia. The step in this research were: maceration to obtain extract chloroform, phitotochemical assay to identify the group of secondary metabolites, and toxicity assay by using Bhrine Shrimp Lethality Test method. It was obtained 46 g of green concentrated exctract of chloroform. The result of phytochemical assay show that the extract contain steroid and alkaloid groups. The crude extract chloroform is toxic against Artemia salina with LC50 value is 53,57 Âµg/ml.